As study on air pollution in Malaysia: caused by smoke vehicles / Nik Mohd Adli Nik Azlan, Nooraneda Mutalip Laidey - Nik Azlan, Nik Mohd Adli; Mutalip Laidey, Nooraneda (2007)
Clean environment is very important to every people in this world. In order to get a clean air to breath, we together need to unite and not to pollute the air. Poorly, nowadays, in many countries all over the world, the air quality is poor in quality. Every minutes of the day, vast quantities of pollutants are pouring into the atmosphere and these pollutants come from both natural and human sources.1 In Malaysia, the definition of pollution is provided in Section 2 of the Environmental Quality Act 1974 as "any direct or indirect alteration of the physical, thermal, chemical, biological, or radioactive properties of any part of the environment by discharging, emitting, or depositing wastes so as to affect any beneficial use adversely, to cause a condition which is hazardous or potentially hazardous to public health, safety or welfare to animals, birds, wildlife, fish or aquatic life, or to plants, or to cause a contravention of nay condition, limitation or restriction to which a license under this Act is subjected". Thus, air pollution literally means air that had been altered by many types of substance and by human conduct. There are contributory factors to air pollution such as smoke that are produce by industries sector, vehicle, and forest fire. Forest fire is the main cause of air pollutant. In Indonesia, it has been occurring almost yearly, especially during the dry season, at certain location in Indonesia. Uncontrolled forest fire has caused smoke pollution throughout other Asian countries including Malaysia. The Coordinator Minister of Social Welfare of Indonesia declared this uncontrolled forest fire, especially in Sumatera and Kalimantan as national disaster.2 This phenomenon directly affected the neighboring country, Malaysia almost yearly and smoke from forest fire had usually cause haze in Malaysia.